Blood Coagulation Favors Anti-Inflammatory Immune Responses in Whole Blood - Victor I. Seledtsov; Anatoly A. Pyshenko; Tatyana Ya. Lyubavskaya; Irina A. Seledtsova; Alexei A. von Delwig (Hematology Reports)
Background: We studied the effects of human blood coagulation on antioxidant activity and the cellular secretion of immunoregulatory molecules in vitro. Methods: Reactive oxygen species (ROS) activity and cytokine content were determined in plasma and serum blood samples incubated with lipopolysaccharide (LPS) for 3 h or 18 h. Results: Coagulation process significantly decreased ROS activity induced by LPS in blood samples from healthy donors. Human serum was found to have significantly higher antioxidant activity than plasma. Blood coagulation markedly reduced LPS-induced secretion of TNF-α by cells, without significantly affecting the secretion of interleukin-1 (IL-1), IL-6, IL-8, or C-reactive protein (CRP). Blood clotting led to an increase in LPS-induced release of vascular endothelial growth factor (VEGF) by blood cells. A significant increase in procalcitonin levels was also observed in serum samples. Conclusions: Blood clotting enhances the antioxidant and anti-inflammatory functions of immunoreactive blood cells.